1943
DOI: 10.1042/bj0370640
|View full text |Cite
|
Sign up to set email alerts
|

Studies in immunochemistry

Abstract: Council for a whole time grant. We should like to express our gratitude to Prof. E. L. Hirst for specimens of d-araboascorbic and d-glucoascorbic acids, and to Prof. T. Reichstein for a specimen of 6-desoxy-l-ascorbic acid. Thanks are also due to Roche Products Ltd. for a gift of 1-ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1945
1945
1978
1978

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The materials were examined for their capacity to inhibit specific haemagglutination as described by Morgan and King [25] using naturally occurring anti-A and anti-B agglutinins in normal human sera for measuring A and B activity. The H activity was measured using a rabbit immune anti-H serum kindly supplied by Professor W. M. Watkins, Lister Institute of Preventive Medicine, London S.W.l.…”
Section: Serological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials were examined for their capacity to inhibit specific haemagglutination as described by Morgan and King [25] using naturally occurring anti-A and anti-B agglutinins in normal human sera for measuring A and B activity. The H activity was measured using a rabbit immune anti-H serum kindly supplied by Professor W. M. Watkins, Lister Institute of Preventive Medicine, London S.W.l.…”
Section: Serological Examinationmentioning
confidence: 99%
“…A methylation study of the bronchial glycoprotein, neuraminidase-digested bronchial glycoprotein and mild acid-hydrolysed bronchial glycoprotein revealed that the N-acetylneuraminic acid was linked to C-3 of penultimate galactose units. Fucose occurs in three different linkages, approximately 50 % is linked to C-2 of penultimate galactose units, approximately 25 % is linked to C-4 of glucosamine residues already substituted at C-3 and the remainder is linked to C-3 of glucosamine residues already substituted at C-4.…”
mentioning
confidence: 99%
“…AnaIytical density gradient sedimentation was performed in a Beckman model E analytical ultracentrifuge [5,6] Serological activity was determined by the capacity of the substances to inhibit in specific haemagglutination tests [17]. Fig.…”
Section: Sedimentationmentioning
confidence: 99%
“…Blood-group serological activities of all individual fucolipids were investigated according to Morgan and King [26] modified as follows. Mixed liposomes of individual glycolipid and sphingomyelin as auxiliary lipid [27] were prepared in NaCl/P, as described previously [5].…”
Section: Hemagglutination Inhibition Testsmentioning
confidence: 99%